ANALISIS KEBIJAKAN PEMBANGUNAN KEPULAUAN SERIBU - Nandang Najmulmunir (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2004)
Small island have special characteristic, which have fragile ecosystems. Kepulauan Seribu having developed in one administrative authority. The management of small island was guided by the principle of sustainable development, which expressed in Government Regulation Number 41/ 2000. In the past decade there were many policies did not fidflll the sustainable principle.